Anxiety and depression in first-year university students: the role of family and social support - Estrella-Proaño, Andrea; Rivadeneira, María F.; Alvarado, Jéssica; Murtagh, Matías; Guijarro, Susana; Alomoto, Lidia; Cañarejo, Glenda (Frontiers in Psychology, 2024)
Adolescents and young are one of the population groups with the highest prevalence of anxiety and depression worldwide. Few studies address this problem in young university students. This study aimed to analyze the prevalence of anxiety and depression in first-year university students and its association with family functionality and social support. A cross-sectional study was carried out on 847 students from five cities in Ecuador, between 18 and 25 years of age, who were beginning their university career. Anxiety and depression symptoms were measured with the Hospital Anxiety and Depression Scale, family functionality with the FF-SIL Test, and social support with the Medical Outcomes Study Scale. The sociodemographic characteristics of the participants were also measured. Bivariate and multivariate data analyzes were performed using logistic regression. The 19.7% of the students presented anxiety, while 24.7% presented depression. Female students, students with poor economic status, and married/in union students had a higher prevalence of anxiety and depression. Family dysfunction and lack of global social support were significantly associated with a higher prevalence of anxiety respectively) and depression (OR 1.87 95% CI 1.16-3.01; OR 2.2 95% CI 1.35-2.57, respectively), regardless of the student's economic situation. In conclusion, social support and family functionality play an important role in the prevention of anxiety and depression in first-year university students. It is necessary to establish mental health policies and strategies in this underserved population group that strengthen social support and family functionality. * P-value statistically significant p<0,05 522 ** P-value statistically significant p<0,01 523 a OR adjusted for sex, age, marital status, and economic and living situation.